Foreign Trade and its Legal Concept (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The Research in this regard is concerned with the importance of foreign trade, which is the solution to the dilemma of states ’inability to achieve self-sufficiency in goods and services on their own because of their inability to produce these goods, either for reasons related to the nature of the goods or the lack of capital, technologies, or modern management in some countries to produce them at a lower cost.The research aims to clarify the role of foreign trade in supplying, developing and supporting the local economy in foreign currencies and to know the most important methods of this trade.The research concluded that foreign trade came in response to the extensive exchanges that occur in the international economy and the challenges that developing countries faced at the economic level represented by the attempt of the industrial capitalist countries to tighten their control over international markets and impose their hegemony on the developing world countries to achieve their interests.